A new hybrid model of software engineering and systems engineering for embedded system development methodology - Suliman A.; Nazri N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Embedded software; Software engineering; Systems analysis; Systems engineering; Development methodology; Development model; Embedded system development; Hybrid model; Non functional properties; Research and development; Software and hardwares; Embedded systems